Opportunities for Energy Efficiency Improvement in a Renewable Fuels Process - Lecerof, Lisa (My University, 2014)
A larger part of the cooling and heating demand in a renewable fuels plant is accomplished by using air-cooling and steam in several alternating steps. This study examine what opportunities there are for energy efficiency improvements on site, in order to reduce the electricity and fuel consumption in the plant. The evaluation was done by using pinch tools on three different case studies: theoretical case based on technical specifications, operational case based on averaged measurements from the process and the adjusted operational case with changed temperature targets respectively. The investigated cases had total heating demands of 18.7 MW, 20.0 MW and 19.2 MW and total cooling demands of 20.4 MW, 18.9 MW and 17.7 MW respectively. Results from the pinch analysis of the theoretical case indicated that there were three ways to improve energy efficiency in the plant: by removal of pinch rule violations, by optimizing the temperature level at which utility was supplied or increasing methanol condensation temperatures in an integrated HEN (i.e. raising saturation pressure). Actual temperatures and flows in the operational case were analysed. By changing target temperatures the plant could save 2 123 kW of energy, both from heating and electricity. Assuming the operation would be adjusted accordingly, the adjusted operational case was created. On this case the full pinch analysis with retrofit suggestions was performed, as well as investigating the full potential of optimizing hot utility levels and condensing methanol at a higher temperature. By performing a retrofit of the existing HEN, 1 517 kW can be heat integrated. This would save the plant 5.54 MSEK annually in reduced utility costs. By heating the two flows entering the reactors with MP steam before using HP steam, 5 100 kW could be saved. This shift of hot utility level would save the plant 3.74 MSEK annually in reduced steam costs. By building two new flashing steps at 8 bar, which would supply condensing methanol at 135ºC, approximately 2 194 kW would become available. If integrated in such a way that it could replace the corresponding load in MP steam, 15.5 MSEK in eliminated steam costs would be saved annually. It was recommended that options for flashing methanol at intermediate pressures, combined with a new retrofit investigation, would be the best alternative to investigated further.
Keywords: Hållbar utveckling; Grundläggande vetenskaper; Energi; Kemiteknik; Sustainable Development; Basic Sciences; Energy; Chemical Engineering